Memorable volunteer trip: Unveiling the experience-mediated model from Gen Z Sharia-driven re-participation - Al Syahr, Salsabila Shabriyyah; Suryawardani, Bethani; Maulidina, Alma Syifa (Faculty of Business & Economics, Universitas Islam Indonesia, 2026)
Purpose – This study aims to examine the role of Sharia-based personal norms (SN) in shaping Muslim Gen Z voluntourists’ re-participation intention (RI) in volunteer tourism (voluntrip), while investigating the mediating role of memorable volunteer tourism experience (MVTE).Methodology – A quantitative approach was employed using survey data collected from 273 Muslim Gen Z voluntourists in West Java, Indonesia. Data were analyzed using partial least squares structural equation modeling (PLS-SEM), complemented by multi-group analysis (PLS-MGA) to assess group differences based on activity orientation and participation duration.Findings – The results reveal that SN influence both the MVTE and RI. Moreover, MVTE serves a complementary partial mediating role in the relationship between personal norms and behavioral intention. This infers that the continuation of voluntrip action hinges on how participation is experienced and remembered. In addition, this study assessed group differences in activity orientation and participation duration. However, no statistically significant differences were found, implying that Muslim Gen Z voluntourists are largely value-driven, with experiences and intentions shaped more by meaningfulness than by contextual factors. Implications – The findings highlight memorable experiences as a partial pathway linking personal norms to sustained participation in voluntourism. Initiators and providers are encouraged to pursue the goal of maslahah by developing impactful and meaningful voluntrip designs.Originality – This study incorporates maqasid al-Sharia on personal norms and investigates the mediating role of memorable experiences on norm activation theory, offering a novel faith-based perspective in voluntourism research and providing a deeper understanding of value-driven experience tourist behavior among Muslim Gen Z.